Comparative Analysis of Traditional and Digital Financial Administration Implementation on MSME Financial Management Effectiveness - Basuki Rahmat (CV Pena Jaya Pers, 2025)
This study aims to compare the implementation of traditional (manual) and digital financial administration in Micro, Small, and Medium Enterprises (MSMEs) and analyze its impact on the effectiveness of MSME financial management. The method used is a comparative literature review examining ten national and international scientific articles published between 2018 and 2025. The analysis is based on effectiveness indicators such as time efficiency, data accuracy, and report preparation speed. The review results indicate that digital systems have higher effectiveness compared to traditional systems across various indicators. However, the implementation of traditional systems remains dominant among MSMEs, primarily due to limited digital literacy, high initial investment costs, and internet accessibility issues in certain regions. Therefore, the conclusion of this study emphasizes the importance of adopting a hybrid system (combining traditional and digital systems) and improving digital financial literacy. This is crucial to ensure that the MSME financial administration process can run more effectively, efficiently, and sustainably.